2021
DOI: 10.1002/ange.202014898
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Molecule Counting Coupled to Rapid Amplification Enables Detection of α‐Synuclein Aggregates in Cerebrospinal Fluid of Parkinson's Disease Patients

Abstract: α‐Synuclein aggregation is a hallmark of Parkinson's disease and a promising biomarker for early detection and assessment of disease progression. The prospect of a molecular test for Parkinson's disease is materializing with the recent developments of detection methods based on amplification of synuclein seeds (e.g. RT‐QuIC or PMCA). Here we adapted single‐molecule counting methods for the detection of α‐synuclein aggregates in cerebrospinal fluid (CSF), using a simple 3D printed microscope. Single‐molecule me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The prominence of each event was plotted against its respective residence time to examine population heterogeneity and provide a single-molecule profile (fingerprint) of the sample, as previously described. 34 Briefly, ThT + particles were classed based on their distribution in each quadrant (Figure 2B) where events were defined as small (S, low prominence, short residence time), high (H, high prominence, short residence time), long (L, low prominence, long residence time), or neutral (N, high prominence, long residence time) with thresholds set at 300 photons and 250 ms, respectively. Our data showed that S type particles were the first to be synthesized during the in vitro oligomer-inducing protocol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prominence of each event was plotted against its respective residence time to examine population heterogeneity and provide a single-molecule profile (fingerprint) of the sample, as previously described. 34 Briefly, ThT + particles were classed based on their distribution in each quadrant (Figure 2B) where events were defined as small (S, low prominence, short residence time), high (H, high prominence, short residence time), long (L, low prominence, long residence time), or neutral (N, high prominence, long residence time) with thresholds set at 300 photons and 250 ms, respectively. Our data showed that S type particles were the first to be synthesized during the in vitro oligomer-inducing protocol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We have established that the detection limit for PFFs using AttoBright was 1 pM monomer equivalent. 34 Our highly sensitive single molecule method was used here to track the aggregation at different steps and to compare the size and reactivity of the different α-syn species (monomers, oligomers and fibrils). After low-speed centrifugation of a 5 h aggregation reaction (18000g for 10 min), many fibrils were still present in the supernatant and dominated the fluorescence time trace (Supporting Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations